Soil moisture studies - Hodgson, Edward Howard (My University, 1903)
Introduction: The importance of the subject of soil moisture has been abundantly shown in many parts of the United States, but is of the greatest importance in the central west where there is such a scarcity and unequal distribution of rainfall, that it becomes necessary to resort to the most practical and scientific methods in order to make agriculture pay on much of the arable land between the Mississippi River and the Rocky Mountains. In much of this comparatively arable territory there is sufficient rain during the year to raise fair crops of many of the cereals, but the unequal distribution of the moisture causes the crop to grow very rank for a time but later it is often impaired by drouth, or entirely dried up before the grain is matured. Many a farmer after putting in his crop and working hard to keep down the weeds has come thoroughly disheartened when the hot, dry months of July and August came; and his corn was withered before the scorching winds leaving him nothing, not even feed for his hungry stock. Perhaps he becomes discouraged and quits farming or he travels on seeking a more favorable farming locality. But here he finds many others before him and many disadvantages. The population is rapidly increasing, the country is fast filling with settlers, the better farming lands have all long since been taken. Some of us must till these less desirable lands, and we find that to raise crops we must practice new methods of farming. These methods in the main are conditions lessening the damage by summer drouths.
Citation: Hodgson, Edward Howard. Soil moisture studies. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Agriculture; Drought; Drouth; Farming; Soil Moisture; Kansas; Theses